Complexity analysis of the Portevin-Le Chatelier in an Al alloy at different temperatures. Issue 2 (February 2021) - Xu, Jianfei; Chen, Guoxiong; Fu, Shihua
Highlights: The complexity of stress curves is quantified by modified multiscale entropy. Three evolutions of entropy with scale are related to different serration types. The evolution of sample entropy is opposite to that of critical strain. The stress serrations with different dynamic characteristics are distinguished. This work provides a new perspective to understand this phenomenon. Abstract: The complexity of the Portevin-Le Chatelier (PLC) effect in an Al alloy at different temperatures was analyzed by modified multiscale entropy. The results show that three evolutions of entropy with scale factor, i.e., near zero, monotonically increasing and peak-shape, were observed corresponding to the smooth curves, type-A serrations and type-B/-C serrations, respectively. The scale factor at the peak was one-third of the average serration period. The sample entropy increased initially and then decreased with temperature, which was opposite to the critical strain. It is also suggested that the type-A serrations corresponded to self-organized criticality and the type-B/-C serrations corresponded to chaos through the evolutions of entropy with scale factor.